AB1093 Efficacy and safety of steroid injections for shoulder pain. (23rd January 2014) - Teixeira, F.; Peixoto, D.; Afonso, C.; Araújo, D.
Abstract : Background: Shoulder pain has been found to be the second most frequent acute musculoskeletal complaint presenting in general practice and the third most common site of musculoskeletal pain in the community. Approximately 10% of people will have one or more episodes of shoulder pain during their lifetime. Although local steroid injections are one of the most common treatments, there is no strong evidence to support their use and they have potential adverse effects. The optimum timing of steroid injections is also still unclear. Objectives: To assess the efficacy and safety of steroid injections for patients with shoulder pain at six, 12 and 18 months after subacromial steroid injection, correlate ultrasound changes and with time course of shoulder pain and treatment outcomes. Methods: In a prospective study, 86 patients with shoulder pain were evaluated for demographic and clinical data and a visual analog scale (VAS) for pain. In all was performed a shoulder ultrasound. Ultrasound operator evaluated for the presence of rotator cuff tendinopathy, tear or impingement, subacromial bursa fluid or wall thickening, abnormalities of the long head of the biceps tendon, or calcification Seventy-four patients underwent a subacromial corticosteroids injection with methylprednisolone, ultrasound guided. Treatment efficacy was evaluated a one month, six, 12 and 18 months. The primary outcome measure was a 10-cm VAS for shoulder pain intensity. The mean age was 67.9±12.4 years and the men disease duration was 25.5±14.5 months. Results: Right shoulder was more commonly involved (74%). Rotator cuff tendinopathy was found in 67%, subacromial bursa fluid in 38%, calcification in 27%, signs of impingement in 42.8%, adhesive capsulitis in 8.9%, partial tears of rotator cuff in 12.5%. Median visual analog scale (VAS) pain score was 8, 4 before treatment, 7.7, 5.4 and 4.1 at 6, 12 and 18 months after treatment, respectively. The patients with subacromial bursa fluid showed a significantly greater improvement in VAS scores compared with patients with not had (p<0.05). In patients with nocturnal pain the treatment response was better (p=0, 06). In patients with calcifications the response was worse (p<0, 05). The patientsunderwent a subacromial corticosteroids injections in first 6 months of disease duration had a better response (p<0, 05) in the shoulder pain reduction. There were no complications observed. Conclusions: The subacromial steroid injection was more effective in patients with subacromial bursa fluid, with nocturnal pain and in the first six months of disease. Patients with calcification in ultrasound had a poor response. The subacromial steroid injection was safe, there were no complications observed Disclosure of Interest: None Declared